2015
DOI: 10.1136/bjsports-2015-094621
|View full text |Cite
|
Sign up to set email alerts
|

Citius, Altius, Fortius: beneficial effects of resistance training for young athletes: Narrative review

Abstract: The motto of the Olympic Games is Citius, Altius, Fortius which is Latin for 'Faster, Higher, Stronger'. It is a clarion call to all competitors, including the youngest, to engage in training strategies that prepare athletes to be the best in the world. Existing research indicates that various forms of resistance training can elicit performance improvements in young athletes. Stronger young athletes will be better prepared to learn complex movements, master sport tactics, and sustain the demands of training an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 96 publications
(101 reference statements)
3
130
0
13
Order By: Relevance
“…There is a common perception among some swim coaches that resistance training will have a negative impact swimming efficiency due to increased drag forces resulting from excessive muscle hypertrophy and a decrease in flexibility [31]. However, in line with the present findings, evidence suggests strength gains in prepubescent individuals are primarily due to neuromuscular changes [32] and researchers and qualified strength and conditioning coaches should work to alleviate this misconception and promote the benefits of resistance training for young athletes [32].…”
Section: Discussionsupporting
confidence: 73%
“…There is a common perception among some swim coaches that resistance training will have a negative impact swimming efficiency due to increased drag forces resulting from excessive muscle hypertrophy and a decrease in flexibility [31]. However, in line with the present findings, evidence suggests strength gains in prepubescent individuals are primarily due to neuromuscular changes [32] and researchers and qualified strength and conditioning coaches should work to alleviate this misconception and promote the benefits of resistance training for young athletes [32].…”
Section: Discussionsupporting
confidence: 73%
“…Although a number of authors have previously discussed the role of long-term athletic development models in developing human performance or sporting talent (9,10,49,92,142,146), it is vital that practitioners acknowledge that the constructs of long-term athletic development are appropriate for youth of all ages and abilities (143). Although a systematic approach to the development of athleticism is required to prepare aspiring young athletes for the demands of sport (69), it is imperative that all youth, including those that are inactive, underweight, overweight, or obese are afforded the same opportunity to engage in dynamic, integrated, and evidence-based training programs that promote the development of both health and skillrelated components of fitness (75,143,144,180,182).…”
Section: Long-term Athletic Development Pathways Shouldmentioning
confidence: 99%
“…A meta-analytical review of 34 training studies showed that pre-and early-pubertal youth achieved resistance traininginduced gains in motor skills that were approximately 50% greater than adolescents (15), thus highlighting the increased trainability of motor skills in children. Aside from the development of athleticism, preparatory conditioning inclusive of motor skill and muscular strength development provides an appropriate strategy for reducing the relative risk of injury for youth during sport and physical activity later in life (69,80,111,112,190). Motor skill competence, and indeed the perception of motor skill competence, is an important antecedent of physical activity during childhood (42, 83,107,135,214,242) and adulthood (140,149).…”
Section: Motor Skill and Muscular Strength Developmentmentioning
confidence: 99%
“…In other sports such as rugby, weight lifting is used to add/maintain functional weight to the athlete and improve power on sport specific tasks is critical. An appropriately structured resistance training program will lead to improved strength partly through improvements in muscle mass [80]. An individual's strength is highly, but not wholly dependent upon muscle mass [81,82].…”
Section: The Molecular Regulation Of Resistance Training Adaptation mentioning
confidence: 99%